CoFe2O4/NiFe2O4 S-scheme composite for photocatalytic decomposition of antibiotic contaminants. Issue 8 (15th April 2023) - Song, Jiahe; Zhang, Jingjing; Zada, Amir; Ma, Yuhua; Qi, Kezhen
Abstract: Keeping in view of the hazardous application of tetracycline hydrochloride antibiotic, an efficient CoFe2 O4 /NiFe2 O4 heterojunction photocatalyst has been prepared hydrothermally by combining CoFe2 O4 and NiFe2 O4 nanoplates. The CoFe2 O4 /NiFe2 O4 composite with the improved photocatalytic activity can be employed for removal of tetracycline hydrochloride antibiotic, comparing to the bare CoFe2 O4 and NiFe2 O4 . The optimized sample 5%-CoFe2 O4 /NiFe2 O4 shows the high photocatalytic degrading tetracycline with 76.1% removal efficiency in 60 min. These improved photocatalytic activities are attributed to the extended visible light absorption and enhanced charge separation following S-scheme route as confirmed from photoluminescence and electrochemical studies. From the charge trapping experiments, it is confirmed that superoxide radical and holes in the valence band of NiFe2 O4 with high thermodynamic energies are responsible for the photodegradation of the target pollutant. This work provides sufficient attention towards the preparation of low cost materials for the removal of highly hazardous pollutants being present in water.